If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -38 + -1x = 10 + -5x Solving -38 + -1x = 10 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -38 + -1x + 5x = 10 + -5x + 5x Combine like terms: -1x + 5x = 4x -38 + 4x = 10 + -5x + 5x Combine like terms: -5x + 5x = 0 -38 + 4x = 10 + 0 -38 + 4x = 10 Add '38' to each side of the equation. -38 + 38 + 4x = 10 + 38 Combine like terms: -38 + 38 = 0 0 + 4x = 10 + 38 4x = 10 + 38 Combine like terms: 10 + 38 = 48 4x = 48 Divide each side by '4'. x = 12 Simplifying x = 12
| q+18=4q-15 | | 4/9x=8/63 | | (24000–X)×(17600/X)=1600 | | 35d=70 | | -9(x+8)=-9x-72 | | 4.7m=43.71 | | 9r+9=5r+49 | | 6(12-2z)=-2z | | Y=-3(x-5)-10 | | 3=21-6a | | -3x+2-5x-7=4+2 | | 6p-49=11p-79 | | 9p+146=8p | | 4x-207=9-5x | | 20x+15y=950 | | z^2+2zi-2=0 | | -9(t^2+13)(t^2-7)=0 | | 48x=4.176 | | -4+14-24=x | | 8v+80=17v-100 | | 3x-11=4x-11 | | 0.05x=0.0815 | | 46b-42b+9b+10b-21b-1=39 | | 19c+45=31c-63 | | 5g+6kg=g | | (X*x)+((3x)*(3x))=(24*24) | | 10b-9b+7b+3b+1=45 | | 45h+11=34h+55 | | 12a-11a-a+11a+3=36 | | 7×1/2= | | (X-3)(x^2+4x+19)=0 | | 5g+6k=g |